Analysis of optimization medical image watermarking using particle swarm optimization based on SLT - Rahmalan, Hidayah; Abdollah, Mohd Faizal; Mohd Kosnin, Zarita; Christy Atika Sari; Eko Hari Rachmawanto (2012)
This paper propose an optimization technique, based on Slantlet Transform (SLT) and Particle Swarm Optimization (PSO). In order to improve the quality image to achieve the imperceptibility without losing robustness, an optimal scheme for embedding the secret message derived from PSO. The propose technique takes an advantages of SLT that was better time localization as an improved version of Discrete Wavelet Transform (DWT). In additional, SLT is a piecewise linear and used two zero moment in which SLT is better signal compression better than DWT and Discrete Cosine Transform (DCT). Meanwhile, PSO as a popular optimization technique and has been successed to use as a method to balance the imperceptibility and robustness, it is because PSO serves the weighting factor inside of embedding process. As we know that there is researcher ever done using SLT and PSO in watermarking, this paper used to investigate the capability of SLT-PSO in order to achieve imperceptibility without losing robustness. The comparison of this technique is displayed in this paper to show the capability of propose technique convince to improve the performance of SLT while the experiment will be implemented using medical images.